Indication, Safety and Clinical Impact of Cardiovascular Magnetic Resonance: A Pilot Run of the First National CMR Registry for Malaysia - Ho, K.H.; Mohd Amin, N.H.; Muhd Apipi, N.A.; Husain, N.L.; Koh, K.T.; Said, A.; Johari, F; Fong, A.Y.Y.; Ong, T.K. (Elsevier, 2017)
Background: Cardiovascular magnetic resonance (CMR) is a rapidly emerging noninvasive imaging technique providing high resolution images without any application of radiation. It has broad range of clinical applications and is increasingly been used in clinical practice in Malaysia. A national CMR Registry is needed to assess its practice in Malaysia. Objective: To evaluate indications, safety and impact on patient management of CMR in Sarawak Heart Centre. Materials Methods: A pilot run of CMR Registry in single centre with consecutive patients who underwent clinical CMR from January-June 2015. Retrospective data collection from CMR database and case notes. Results: A total of 169 patients underwent clinical CMR, with 20 did not complete scan; 25% due to claustrophobia. 94% of patients received gadolinium-based contrast agent. Most important indications were viability assessment (54.4%), cardiomyopathy (28.2%), and risk stratification in suspected coronary artery disease (CAD) (4.7%). 6.7% of patients underwent stress MR (adenosine or dobutamine). Severe complications only occurred in 0.7% of the cases (anaphylactic reaction secondary to contrast agent). No mortality during/due to CMR. There was direct impact of CMR on the clinical management by confirming suspected diagnosis (59.1%), excluding suspected diagnosis (21.5%), providing additional information for suspected diagnosis which is confirmed or excluded (18.1%) and providing unsuspected completely new diagnosis (1.3%). Invasive coronary angiogram was avoided and diagnosis were excluded in all patients referred for risk stratification of suspected coronary artery disease. Invasive therapeutic procedures such as PCI, CABG, valve surgerywere triggered in 49.6 % of patients after CMR was done, regardless of indication. Out of 81 patients who underwent CMR for viability study, 76.5% were planned for revascularisation (CABG or PCI) with the restwere planned for optimalmedical therapy only after the CMR. Conclusions: The top indications of CMR in Sarawak are viability assessment, cardiomyopathy and risk stratification in suspected CAD, which differs from the EuroCMR registry results. This demonstrated the importance of establishing a national multicentre CMR registry in Malaysia, and subsequently substudy on specific conditions. With appropriate medical personnel training and patient selection, CMR is safe and has strong impact on clinical management.